The Role of Supervision in Improving Employee Work Discipline in the Sinjai Regency DPRD Secretariat - Jamaluddin, Jamaluddin; Tiawan, Agus; Nasrullah, Muh.; Suprianto, Suprianto (Universitas Negeri Makassar, 2023)
The role of supervision in improving employee discipline in the Sinjai Regency DPRD Secretariat. This research is a type of descriptive research, aimed at determining the role of supervision in improving employee discipline in the Sinjai Regency DPRD Secretariat. There are informants in this study, namely the Secretary of the Sinjai Regency DPRD, the Head of the Supervision and Budgeting Facilities Section, the Head of the Trial and Legislation Sub-Division, the Legislative Drafting Analysis Section Employee , the Legislative Drafting Section Employee. The data collection techniques used are observation, interviews and documentation. Data analysis techniques used, namely data collection, data condensation, data presentation and conclusion/verification. The results showed that supervision in the secretariat of the Sinjai Regency DPRD played a very important role in improving employee work discipline, judging from the indicators, namely setting standards for implementation or planning, work measurement, work assessment and corrective actions. Because by supervising, it will assess the work activities carried out by employees so that they will know the extent of employee work performance. Therefore, by conducting supervision, it will be easier to prevent if at any time in the implementation of activities there are irregularities committed by employees.